Amazoboea, a new genus of Darwin wasps (Hymenoptera, Ichneumonidae) from western Amazonia - Sääksjärvi, Ilari E.; Broad, Gavin R.; Veijalainen, Anu; Österman, Emil M.; Kaunisto, Kari M. (Pensoft Publishers, 2026)
We describe a new monotypic genus of Darwin wasps (Hymenoptera, Ichneumonidae, Banchinae) from the Yasuní region, Ecuador: Amazoboea gen. nov. is described to accommodate A. selva sp. nov. The new genus was discovered from samples collected by canopy fogging in lowland rainforest. Amazoboea is placed in the tribe Atrophini where it is morphologically very distinctive and easily separated from all other banchine genera. Through the description of Amazoboea, we aim to draw attention to the considerable, yet little-known and threatened, fauna of Amazonian Darwin wasps.